PENGALAMAN GURU MENGAJARKAN PENCEGAHAN KEKERASAN SEKSUAL PADA ANAK USIA PRA SEKOLAH - Dyah Rahmawatie (Jurnal Ilmu dan Teknologi Kesehatan, 2016)
Sexual abuse among children can be harmful to the children’s subsequent growth anddevelopment The increased incidence of sexual abuse among children encourages theearly prevention attempt. Teachers have responsibility for the preventing Sexual Abuseamong Children when parents took a part yet because of parent’s taboo perception.Teacher’s experience was very usefull for next education in children sexual abuseprevention. The purpose of this study is to explore teacher’s experience in teaching theprevention of sexual abuse among pre-school age children This study use a qualitativemethod with descriptive phenomenological approach. Participants of the study consisted ofseven teacher from Wijaya Kusuma group. Data is collected by focuss group discussionand interviews. Data is analyzed according to Collaizzi’s stage data analysis. The findingof this study include education model preventing sexual abuse, source of teachersmotivation on preventing sexual abuse and teacher difficulties on preventing sexual abuseamong presschool children.